(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This experimental work aims to examine the effect of nanoparticles added to diesel fuel on engine emission characteristic. Nano fuels are prepared by adding Al2O3 or TiO2, both with particle size less 45nm to diesel fuel. Four doses for each type namely (25, 50, 100 and 150) ppm are prepared. These nanoparticles are blended with diesel fuel in varying volume fraction by the means of an electric mixer and an ultrasonicator (JTS-1018). Their stability characteristics were analyzed under static conditions. The Nano fuels are (DF+Al2O3) and (DF+TiO2). The study shows that the addition of nanoparticles to diesel fuel improves in physical properties such as cetane number where it increases from 51.6 to 54.3 for Al2O3 at 150ppm. Also Comparisons of fuel properties without and with nanoparticles additives (Al2O3 and TiO2) are presented. The influence of nanoparticles addition is very clear on the emission characteristics. The results show that the Al2O3 and TiO2 reduce the CO emission by 34% and 25% respectively at 75% load and 25ppm. The NOx emission is increased with Al2O3 by 4.12% at 25ppm and full load, but with the TiO2 is decreased by 10.56% at same operating conditions. The reduction of smoke opacity with Al2O3 and TiO2 is 28% and 25% respectively.